2017
DOI: 10.1038/nsmb.3484
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for GABAA receptor potentiation by neurosteroids

Abstract: Type A γ-aminobutyric acid receptors (GABARs) are the principal mediators of inhibitory neurotransmission in the human brain. Endogenous neurosteroids interact with GABARs to regulate acute and chronic anxiety and are potent sedative, analgesic, anticonvulsant and anesthetic agents. Their mode of binding and mechanism of receptor potentiation, however, remain unknown. Here we report crystal structures of a chimeric GABAR construct in apo and pregnanolone-bound states. The neurosteroid-binding site is mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
178
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(196 citation statements)
references
References 65 publications
13
178
0
5
Order By: Relevance
“…The mechanism by which CORT modulates I Tonic is unknown, but a recent study found a neurosteroid binding site within a conserved transmembrane region of α5 GABA A Rs (Miller et al . ). Furthermore, the 3α and 5α reductases responsible for production of neurosteroids also convert CORT to 3α, 5α tetrahydrocorticosterone (3α, 5α THB) (Traish et al .…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism by which CORT modulates I Tonic is unknown, but a recent study found a neurosteroid binding site within a conserved transmembrane region of α5 GABA A Rs (Miller et al . ). Furthermore, the 3α and 5α reductases responsible for production of neurosteroids also convert CORT to 3α, 5α tetrahydrocorticosterone (3α, 5α THB) (Traish et al .…”
Section: Discussionmentioning
confidence: 97%
“…This structure shows a wide open activation gate in the M2 9 /13 region, but a hydrophobic constriction at the −2 proline, where the pore radius narrows down to 1.6Å, thereby precluding the flow of chloride ions whose Pauling radius is 1.8Å. More recently, several pLGICs have been solved in similar conformations: the human α3 GlyR in complex with both glycine and a positive allosteric modulator, AM-3607 (Huang et al 2017), as well as a GLIC-(GABA A α1) and a (GABA A β3)-(GABA A α5) chimera, the former carrying a α1 G258V mutation promoting desensitization (Laverty et al 2017;Miller et al 2017). All these structures show a conserved pore conformation and were assigned to a desensitized state, since they correspond to agonist-bound shut states.…”
Section: Structural Data Corroborate the Desensitization Gate Modelmentioning
confidence: 99%
“…; Miller et al . ). All these structures show a conserved pore conformation and were assigned to a desensitized state, since they correspond to agonist‐bound shut states.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…How are these processes influenced by endogenous modulators, such as neurosteroids (i.e. GABA A R-pregnanolone interaction; [56])?…”
Section: Small Molecule Ligands and Plgic Function: Outlookmentioning
confidence: 99%